Conspiracy And Populist Narratives in Romanian-Language Contexts: Romania and the Republic of Moldova - Onoriu Colacel (Codrul Cosminului)
This paper investigates the discursive interconnections between conspiracy theories and populism in Romanian-language contexts, encompassing both right-wing and left-wing ideologies. Employing interdiscursive analysis, it explores how these narratives converge to shape and reinforce shared identity discourses from Romanian literary culture to Romanian language mainstream media. While the relationship between right-wing populism and conspiracy theories has been extensively documented, the interplay between left-wing populism and conspiratorial thinking in Romania and the Republic of Moldova remains understudied. This qualitative analysis builds on the concept of cultural populism to examine the long-term synchronisation of literary culture and media discourse, particularly in relation to national self-identification. This case study demonstrates how the dissemination of conspiracy theories and populist narratives in Romanian-speaking cultures perpetuates an ethnocentric collective identity, mainly through right-wing ideological tropes. By giving a glimpse into interdiscursive dynamics, the paper contributes to understanding the use value of literary culture in mainstream political discourse across Romanian-speaking societies.